2013
DOI: 10.1136/jmedgenet-2013-101712
|View full text |Cite
|
Sign up to set email alerts
|

Somatic point mutations occurring early in development: a monozygotic twin study

Abstract: The identification of somatic driver mutations in cancer has enabled therapeutic advances by identifying drug targets critical to disease causation. However, such genomic discoveries in oncology have not translated into advances for non-cancerous disease since point mutations in a single cell would be unlikely to cause non-malignant disease. An exception to this would occur if the mutation happened early enough in development to be present in a large percentage of a tissue's cellular population. We sought to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…The average somatic mutation rate has been reported to be 7.7×10 −10 20. A more recent study that surveyed the whole genome estimated the somatic mutation rate for common SNPs in healthy monozygotic twins to be 1.2×10 −7 per base pair 12. Conrad and his colleagues distinguished the germline and non-germline (somatic and cell line derived) mutations through whole-genome sequencing of a CEU trio and provided a rate of 2.52×10 −7 per nucleotide for non-germline mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average somatic mutation rate has been reported to be 7.7×10 −10 20. A more recent study that surveyed the whole genome estimated the somatic mutation rate for common SNPs in healthy monozygotic twins to be 1.2×10 −7 per base pair 12. Conrad and his colleagues distinguished the germline and non-germline (somatic and cell line derived) mutations through whole-genome sequencing of a CEU trio and provided a rate of 2.52×10 −7 per nucleotide for non-germline mutations.…”
Section: Discussionmentioning
confidence: 99%
“…RAF is the total number of reads supporting the reference allele as a fraction of total number of reads supporting both reference and alternative allele 12. For the putative de novo SNVs that are present in a heterozygous state, RAF threshold was determined as 0.5–0.7 for the twins and 0.95–1.0 for the parents.…”
Section: Study Samples and Methodsmentioning
confidence: 99%
“…A further false assumption, not highlighted in our study, is that fused placentas in DZ twins could be misclassified as monochorionicity. In addition, in rare circumstances, MZ (Edwards et al, 1966) or monochorionic (Umstad et al, 2012) twins may be of opposite sex (Edwards et al, 1966;Umstad et al, 2012) and mosaicism (Li et al, 2014;Petersen et al, 2014) or chimerism (Fumoto et al, 2014;Lee et al, 2014;Waszak et al, 2013) could potentially confound zygosity tests.…”
Section: Discussionmentioning
confidence: 99%
“…Germ line selection for dominant mutations in the male spermatogonia, resulting in high frequencies of single base pair changes for several disorders of fibroblast growth factor-RAS pathways, especially achondroplasia, is well described (reviewed in [15]). A study of 33 identical twin pairs found somatic differences for only two genes [16] and these were not mosaic suggesting very early events. The full answer to the question of possible selection for somatic clones would probably require post-mortem examination of many samples of many tissues.…”
Section: Introductionmentioning
confidence: 96%